Daughters of the Dust (Julie Dash, 1991), le récit d’esclave revisité - Delphine Letort (Amnis)
Julie Dash dedicated Daughters of the Dust to the female members of the black community, endeavouring to uncover the secrets of their common history turned into a taboo subject by the silence that enshrouds the issue of femininity at the time of slavery. The film focuses on the Peazant family who are divided on the eve of their migration to the north: some are afraid to see the family spread apart (Nana) while others look forward to a new beginning (Viola, Haagar). Julie Dash uses the figure of migration to fathom out the complexities of African American identity. Whilst allowing women to address their most intimate dilemmas (rape, skin colour, pregnancy, sexuality, gender roles), the director tries to undermine Hollywood stereotypes of black women. Not only does she look back into the past as a source of inspiration and creation, but she also generates a longing for an idealized tribal life that never was but in the imaginary construct of afrocentrist theorists.